2003
DOI: 10.1046/j.1365-2788.2003.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Referral trends of people with intellectual disabilities and psychiatric disorders

Abstract: Significant trends in referrals were identified, which may be explained by various external factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Psychotropic drugs use was found as 20.4% of MR cases in our sample and this ratio is relatively low, compared to above-mentioned rates, due to less comorbidity we found. Most commonly pharmacological agents used in this area were reported as antipsychotics, benzodiazepines, lithium, antiepileptic drugs, tricyclic antidepressants and SSRIs [18]. Likewise, in our study, the most commonly used psychotropic drugs were antipsychotics, followed by MPH and SSRIs.…”
Section: Discussionsupporting
confidence: 68%
“…Psychotropic drugs use was found as 20.4% of MR cases in our sample and this ratio is relatively low, compared to above-mentioned rates, due to less comorbidity we found. Most commonly pharmacological agents used in this area were reported as antipsychotics, benzodiazepines, lithium, antiepileptic drugs, tricyclic antidepressants and SSRIs [18]. Likewise, in our study, the most commonly used psychotropic drugs were antipsychotics, followed by MPH and SSRIs.…”
Section: Discussionsupporting
confidence: 68%
“…(1997), also found that people with mild intellectual disabilities had a higher probability of contact with generic mental health services. However, unlike Bouras et al. (2003), they also reported that being older and living alone predicted the receipt of psychiatric treatment.…”
Section: Introductionmentioning
confidence: 86%
“…1997; Jacobson 1998). A study of more than 700 referrals to a mental health service for people with intellectual disabilities found that the majority of the referrals were male (60%) and a large percentage were young adults (mean age 33 years) (Bouras et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There were 147 people with autism and ID and 605 people with ID and without autism between 16 and 84 years old (mean = 33.3, SD = 13.2), 60% were males and 40% females They were referred for assessment to a Specialist Mental Heath Service of SouthEast London between 1983(Bouras et al, 2003 and represented 19.5% of the total referrals to the Service for that period. The largest proportion of referrals came from Primary Care (47.5%) followed by Generic Mental Health Services (37.4%) and Social Services (15.2%).…”
Section: Methods Participantsmentioning
confidence: 99%